Performance evolution of spin valve transistor - Rashid, Shahriar; Sobnom, Sinthia; Chowdhury, Mahadi Hasan; Shamrose, Sanjana (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.